Staad Pro Max - Sierra García, Noé; Monroy Miranda, Fernando (My University, 2008)
Definition of Loads Dead Load of a building is the weight of all permanent construction as a floor, roof, framing and covering members. Roof live loads means all loads, including snow, exerted on a roof, except dead, wind and lateral loads. Seismic loads is the assumed lateral load acting in any horizontal direction on the structural system due to the action of earthquakes. Wind load is the load caused by the wind blowing from any horizontal direction. Auxiliary loads are all specified dynamic live loads, other than the basic design loads which the building must safely withstand, such as cranes, material handling systems, and impact loads.
Keywords: Staad pro max; Loads, deflection, metal buildings, enclosed buidings, types of buildings, design loads, metal buiding system nomenclature